MANAGEMENT OF ELECTRICAL ENERGY STORAGE SYSTEMS - M. V. Melikuziev (Modern American Journals, 2025)
The rapid development of renewable energy technologies and the increasing demand for a stable and reliable electricity supply have led to significant interest in the deployment of electrical energy storage systems (EESS). These systems play a critical role in modern power systems by mitigating the variability of renewable energy sources, enhancing grid stability, and improving the efficiency of energy distribution. As electricity demand fluctuates throughout the day, EESS provide a flexible solution to balance supply and demand by storing excess energy during low-demand periods and delivering it during peak hours [1-4].Moreover, the integration of EESS into generation, transmission, and distribution stages of the power system allows for a more resilient and intelligent energy infrastructure. This integration not only supports the seamless incorporation of solar and wind energy but also contributes to the optimization of load profiles, frequency regulation, and voltage control. As a result, EESS are becoming an indispensable component in the evolution of smart grids and sustainable energy systems. This paper aims to explore the principles of EESS management, its impact on the electricity grid, and a proposed control scheme to enhance the operational performance of the entire power delivery chain [4-5].